2022
DOI: 10.3389/fvets.2021.789137
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Right Ventricular Function, Blood Lactate Levels, and Serum Peptidomics Profiles Associated With Mitral Valve Disease in Dogs

Abstract: BackgroundDegenerative mitral valve disease is a common heart problem in dogs. The aims are to evaluate the relationships between right and left ventricular function, and blood lactate concentrations, assess prognostic contribution, and investigate whether serum peptidomics profile could reveal markers or determine the stage in dogs with valve degeneration.Materials and MethodsNinety-three dogs were evaluated in this study. Thirty-nine dogs' serum was collected and analyzed using matrix-assisted laser desorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A previous study reported that TAPSE <110 mm showed right ventricle dilation at the basal level and a worse degree of tricuspid regurgitation. In addition, isovolumic relaxation time (IVRT) and the E/A ratio are important echocardiography parameters for indicating an impairment of diastolic function (Petchdee et al, 2022). Not only the severity of valve regurgitation but also heart function, such as contraction and relaxation, must be considered.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported that TAPSE <110 mm showed right ventricle dilation at the basal level and a worse degree of tricuspid regurgitation. In addition, isovolumic relaxation time (IVRT) and the E/A ratio are important echocardiography parameters for indicating an impairment of diastolic function (Petchdee et al, 2022). Not only the severity of valve regurgitation but also heart function, such as contraction and relaxation, must be considered.…”
Section: Resultsmentioning
confidence: 99%